2022
DOI: 10.25122/jml-2021-0158
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and seasonal pattern of enteric viruses among hospitalized children with acute gastroenteritis in Samawah, Iraq

Abstract: Almost all of the deaths happening under the age of 5 occur in the developed countries of Africa and Asia. This study included children admitted to the surgical care, aged 6 months to 5 years, who suffered from acute gastroenteritis and received treatment at Samawah, Iraq, from December 2018 to December 2019. Test results detected different types of rotaviruses, adenoviruses, astroviruses using ELISA. 56.6% of the infections were attributed to a viral pathogen. The main cause was attributed to rotavirus and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…The peak incidence rate was noted in 29.48% of patients during autumn, 19.28% during the winter, and 08.91% during spring. The lowest incidence rate, 7.38%, was observed during the summer season, and our results are in consensus, as reported by other studies [57]. Likewise, we also observed a significant monthly variation of adenovirus infections; a high frequency was noted during September 40.74%, January 33.33%, October 26.08%, and November 21.42%.…”
Section: Discussionsupporting
confidence: 92%
“…The peak incidence rate was noted in 29.48% of patients during autumn, 19.28% during the winter, and 08.91% during spring. The lowest incidence rate, 7.38%, was observed during the summer season, and our results are in consensus, as reported by other studies [57]. Likewise, we also observed a significant monthly variation of adenovirus infections; a high frequency was noted during September 40.74%, January 33.33%, October 26.08%, and November 21.42%.…”
Section: Discussionsupporting
confidence: 92%
“…Also, Thwiny et al. in Iraq described that the prevalence of rotaviruses, adenoviruses, and astroviruses was higher in the cold seasons of the year [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3] In studies conducted in different countries, the prevalence of rotavirus was reported to vary from 9.7% to 35.9% and the prevalence of adenovirus from 2.5% to 17.1%. [3,[10][11][12][13][14][15] In studies conducted in different regions in Türkiye, rotavirus and adenovirus frequency rates were reported to vary from 6.7% to 20.2% and from 1.3% to 17.6% respectively. [4,[16][17][18][19][20] The difference in results of these studies may be due to both regional, climatic and socio-economic factors, and diagnostic methodology.…”
Section: Discussionmentioning
confidence: 99%